Method for degrading micro-plastic by using composite semiconductor photocatalyst
By using composite materials of copper oxide and titanium dioxide as photocatalytic degradation of microplastics in the prior art, the problems of low efficiency and high cost of photocatalytic degradation of microplastics in the prior art are solved, and efficient, environmentally friendly and economical microplastic degradation effect is achieved.
Patent Information
- Application Number
- CN202411777240.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
Existing photocatalysts are inefficient and costly when degrading microplastics, and may produce harmful by-products, making it difficult to achieve environmentally friendly and economical treatment effects.
A composite material of copper oxide and titanium dioxide is used as a photocatalyst. The catalyst is prepared by calcining method, and the microplastic is pretreated in the alkali solution, and then the photocatalytic degradation is performed using a xenon lamp to simulate sunlight.
The light absorption range and catalytic activity of the photocatalyst are improved, the rapid degradation of microplastics is achieved, the production and operation costs are reduced, and the reaction conditions are mild and no toxic substances are produced.
Smart Images

Figure CN119588353A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the application field of photocatalytic degradation of pollutants, and more specifically, relates to a method for degrading microplastics using a composite semiconductor photocatalyst. Background Art
[0002] Photocatalysis is a technology that uses semiconductor materials to achieve light-induced decomposition of water and organic pollutants. It has no secondary pollution and no energy consumption, and has broad application prospects in the fields of environmental protection and energy conversion. In recent years, plastic, as a cheap, versatile and durable material, has become an indispensable part of modern social life. According to statistics, the global production of plastics in 2019 has reached nearly 370 million tons, and it is showing a growing trend. However, these advantages have also led to a large number of plastic products entering the environment, especially into marine and terrestrial ecosystems. These plastic wastes not only form large garbage belts on the surface of the ocean, but also decompose into microplastics, enter the marine food chain, and have direct and indirect effects on marine life. On land, plastic waste is also common in cities, rivers and remote areas, and even floats in the atmosphere, which eventually leads to their long-term accumulation in the environment and transfer through the food chain, causing various toxic effects, posing a threat to soil quality and biodiversity. Taking the northwest Pacific as an example, the highest proportion of microplastics is fibrous rayon (67%) and polyethylene terephthalate (23%), and the main type of polymer in the atmosphere is PET. At present, the treatment methods for waste plastics include landfill incineration, mechanical degradation, thermal degradation, biodegradation, chemical recycling, etc. Although these methods can effectively reduce the negative impact of plastic waste on the environment and health, they will produce additional pollutants during degradation and consume a lot of energy.
[0003] At present, titanium dioxide is one of the most widely used photocatalysts due to its advantages such as non-toxicity, low price and good chemical stability. However, titanium dioxide mainly absorbs ultraviolet light, which has a narrow range of light utilization. In addition, the electron-hole pairs generated by a single titanium dioxide material in the photocatalytic process are easy to recombine, resulting in low photocatalytic efficiency. Composite materials can overcome these shortcomings and improve their application performance in the field of photocatalysis. Therefore, it is extremely important to develop a catalyst with low cost, simple preparation process and no secondary pollution to the environment for photocatalytic degradation of plastic pollutants. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a method for degrading microplastics using a composite semiconductor photocatalyst, wherein a composite material of copper oxide and titanium dioxide is used as a catalyst. The method is used to photocatalytically degrade microplastics, which has the advantages of simple process, low price, and environmental protection, and has a good application prospect in the actual treatment of plastic pollutants. The photocatalytic degradation used in the present invention utilizes abundant natural renewable energy solar energy, and no or less harmful byproducts are produced during the degradation process. Therefore, it is an energy-saving, environmentally friendly and inexpensive method that can be promoted for use.
[0005] Technical solution: A method for degrading microplastics using a composite semiconductor photocatalyst, comprising the following steps:
[0006] 1) Preparation of composite semiconductor photocatalysts
[0007] The two materials in the catalyst, transition metal copper powder and semiconductor material titanium dioxide, are treated by calcination to obtain catalysts mixed and calcined in different proportions, wherein the mass ratio of copper powder to titanium dioxide is 0.5:1 to 2:1; preferably, the mass ratio of copper powder to titanium dioxide is 1:1;
[0008] 2) Pretreatment of microplastics
[0009] The microplastics were pretreated by alkaline solution treatment, the alkaline solution was 10M KOH solution, the solution content was 50ml, the amount of microplastics added was 2g, the mixture was stirred at a constant temperature of 60°C for 2h, and after cooling, it was directly used as a reaction raw material;
[0010] 3) Add photocatalyst to photocatalytically degrade microplastics
[0011] The photocatalyst is added to the alkaline solution containing microplastics treated with alkali in step 2), and the microplastics are photocatalytically degraded using a xenon lamp to simulate sunlight, wherein the light intensity is 600 mW / cm 2 , the reaction time is 2h. The amount of photocatalyst added is 100mg.
[0012] Further, the treatment of the catalyst in step 1) of the present invention comprises the following steps:
[0013] S1. Disperse copper powder and titanium dioxide in anhydrous ethanol and continue stirring;
[0014] S2. The solution obtained in S1 was filtered under reduced pressure to obtain a filter cake;
[0015] S3. The filter cake obtained from S2 was placed in a drying oven for drying;
[0016] S4. Pour the powder obtained by drying S3 into a crucible, put it into a muffle furnace for calcination, and obtain a composite semiconductor photocatalyst after cooling.
[0017] Furthermore, in the above step S1, the amount of anhydrous ethanol is 150 ml, and the stirring time is 2 h; in the step S3, the drying temperature is 50° C., and the time is 6 h; in the step S4, the calcination temperature is 450° C., and the time is 2 h.
[0018] 4) Performance characterization of composite semiconductor catalysts
[0019] The composite semiconductor catalysts obtained at different mixing ratios were characterized by SEM, TEM, XPS, UV-Vis and electrochemically tested by EIS and It.
[0020] 5) Characterization of microplastics before and after degradation
[0021] The weight loss rate of microplastics subjected to photocatalytic degradation under different reaction conditions was calculated and characterized by SEM.
[0022] Compared with the prior art, this solution has the following beneficial effects:
[0023] (1) This scheme uses a composite semiconductor photocatalyst, and the CuO / TiO2 composite material can efficiently degrade microplastics under the irradiation of visible light. Compared with traditional single semiconductor catalysts, the composite material has a wider light absorption range and significantly improved catalytic activity, thereby achieving a faster degradation process.
[0024] (2) The composite semiconductor photocatalyst used in this scheme is abundant in source, low in price, and has a simple preparation process. It reduces the cost of production and operation, has good economic efficiency, and is a photocatalyst suitable for large-scale promotion.
[0025] (3) This scheme has mild reaction conditions, no toxic substances are produced, the operation process is simple, and the degradation effect on microplastics is excellent. It is an effective solution for treating plastic waste with high economic benefits and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings are for illustrative purposes only and should not be considered as limiting the present invention. In order to more clearly illustrate the present invention, some parts in the accompanying drawings may be omitted, enlarged or reduced, which does not represent the size of the actual product. In addition, the positional relationships shown in the accompanying drawings are for illustrative purposes only and should not be considered as limiting the present invention.
[0027] Figure 1 The XRD diagrams of the composite semiconductor catalyst CuO / TiO2 and the original TiO2 in Examples 1, 2, 3 of the present invention and Comparative Example 2 show that Cu is completely oxidized to CuO and combines with TiO2 to form a composite material;
[0028] Figure 2The electrochemical test diagrams of the composite semiconductor catalyst CuO / TiO2 and the original TiO2 in Examples 1, 2, 3 and Comparative Example 2 of the present invention are shown in Figure a. The CuO / TiO2-1 composite material has a higher light response ability and better stability. Figure b shows that the electron transfer resistance value (R ct ) is smaller and has better conductivity;
[0029] Figure 3 The UV-Vis graphs of the composite semiconductor catalyst CuO / TiO2 in Examples 1, 2, and 3 of the present invention and the original TiO2 in Comparative Example 2. Graph a shows that the combination of CuO enhances the visible light absorption range of the material and improves the visible light utilization rate of the material. Graph b shows that the band gap energy of the CuO / TiO2-1 composite material is smaller than that of TiO2, making it easier for electrons and holes to be excited;
[0030] Figure 4 This is a SEM image of the composite semiconductor catalyst CuO / TiO2-1 in Example 2 of the present invention. The images of different scales show that the white TiO2 particles are relatively evenly attached to the CuO, and Cu forms a porous oxide during the oxidation process;
[0031] Figure 5 This is a TEM image of the composite semiconductor catalyst CuO / TiO2-1 in Example 2 of the present invention. The crystal planes and lattice spacing of the two materials indicate that good contact is formed between TiO2 and CuO;
[0032] Figure 6 The XPS graphs of the composite semiconductor catalyst CuO / TiO2-1 in Example 2 of the present invention and the original TiO2 in Comparative Example 1 are shown in Figure a. The full XPS spectra of the two materials prove the element purity in the composite material. The high-resolution spectra of Ti 2p, O1s and Cu 2p of the two materials are shown in Figure bd, indicating that copper is in the +2 oxidation state and there is a Cu-O-Ti bond, proving that TiO2 and CuO are well combined;
[0033] Figure 7 The SEM images of the microplastics in Example 2 of the present invention and Comparative Examples 1 and 2 show the changes in the surface morphology of PET under different conditions, proving that the CuO / TiO2-1 composite material has a good degradation effect on PET. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below in conjunction with the accompanying drawings. In the embodiment of the present invention, the composite semiconductor photocatalyst includes transition metal copper powder and semiconductor material titanium dioxide, and the microplastic is polyethylene terephthalate particles with a particle size of about 100 μm.
[0035] First, the composite semiconductor photocatalyst of the present invention is obtained by treating copper powder and titanium dioxide, and the treatment comprises the following steps:
[0036] S1. Disperse copper powder and titanium dioxide in anhydrous ethanol and continue stirring;
[0037] S2. The solution obtained in S1 was filtered under reduced pressure to obtain a filter cake;
[0038] S3. The filter cake obtained in S2 is placed in a drying oven for drying;
[0039] S4. Pour the powder obtained by drying S3 into a crucible, put it into a muffle furnace for calcination, and obtain a composite semiconductor photocatalyst after cooling.
[0040] Secondly, the obtained composite semiconductor photocatalyst is used to degrade microplastics, including the following steps:
[0041] 1) Pretreatment of microplastics
[0042] Microplastics were pretreated with alkaline solution;
[0043] 2) Add photocatalyst to photocatalytically degrade microplastics
[0044] The photocatalyst is added to the alkaline solution containing microplastics that has been treated with alkali in step 1), and the microplastics are photocatalytically degraded using a xenon lamp to simulate sunlight.
[0045] Embodiment 1:
[0046] This embodiment adopts the calcination method to prepare the composite semiconductor photocatalyst, and adopts the alkaline solution treatment method to pretreat the microplastics. The calcination method refers to: adding copper powder and titanium dioxide to 150ml of anhydrous ethanol in different mass ratios, stirring for 2h, and filtering under reduced pressure after mixing evenly. The obtained filter cake is dried in a drying oven at 50°C for 6h, and the dried powder is poured into a crucible, placed in a muffle furnace, calcined at 450°C for 2h, and cooled to obtain a composite semiconductor photocatalyst. The alkaline solution treatment method refers to: adding 2g of microplastics to a 10M, 50ml KOH solution, stirring at a constant temperature of 60°C for 2h, and directly using it as a reaction raw material after cooling.
[0047] In this embodiment, the mass ratio of copper powder to titanium dioxide is 0.5:1, which is recorded as CuO / TiO2-0.5.
[0048] Add 100 mg of CuO / TiO2-0.5 composite semiconductor photocatalyst to the pretreated microplastic alkaline solution, place it on a magnetic stirrer, and place it under a xenon lamp at 600 mW / cm 2 The light intensity is 2h.
[0049] Embodiment 2:
[0050] In this embodiment, a calcination method is used to prepare a composite semiconductor photocatalyst, and an alkaline solution treatment method is used to pretreat microplastics.
[0051] In this embodiment, the mass ratio of copper powder to titanium dioxide is 1:1, recorded as CuO / TiO2-1.
[0052] Add 100 mg of CuO / TiO2-1 composite semiconductor photocatalyst to the pretreated microplastic alkaline solution, place it on a magnetic stirrer, and place it under a xenon lamp at 600 mW / cm 2 The light intensity is 2h.
[0053] Figure 4 The SEM image of the composite semiconductor catalyst CuO / TiO2-1 in Example 2 of the present invention is shown. The images of different scales show that the white TiO2 particles are relatively evenly attached to the CuO, and Cu forms a porous oxide during the oxidation process;
[0054] Figure 5 The TEM image of the composite semiconductor catalyst CuO / TiO2-1 in Example 2 of the present invention is shown. The crystal planes and lattice spacing of the two materials indicate that good contact is formed between TiO2 and CuO;
[0055] Embodiment 3:
[0056] In this embodiment, a calcination method is used to prepare a composite semiconductor photocatalyst, and an alkaline solution treatment method is used to pretreat microplastics.
[0057] In this embodiment, the mass ratio of copper powder to titanium dioxide is 2:1, recorded as CuO / TiO2-2.
[0058] Add 100 mg of CuO / TiO2-2 composite semiconductor photocatalyst to the pretreated microplastic alkaline solution, place it on a magnetic stirrer, and place it under a xenon lamp at 600 mW / cm 2 The light intensity is 2h.
[0059] Embodiment 4:
[0060] In this embodiment, a calcination method is used to prepare the photocatalyst, and an alkaline solution treatment method is used to pretreat the microplastics.
[0061] In this embodiment, the amount of titanium dioxide added is 0, which is recorded as CuO.
[0062] Specific preparation of the catalyst: Pour copper powder into a crucible, put it into a muffle furnace, and calcine at 450°C for 2h.
[0063] Add 100 mg of CuO photocatalyst to the pretreated microplastic alkaline solution, place it on a magnetic stirrer, and place it under a xenon lamp at 600 mW / cm 2 The light intensity is 2h.
[0064] Comparative Example 1:
[0065] The microplastics were washed several times with anhydrous ethanol and deionized water, and then dried to obtain the original microplastics without any treatment.
[0066] Figure 6 The XPS graphs of the composite semiconductor catalyst CuO / TiO2-1 in Example 2 of the present invention and the original TiO2 in Comparative Example 1 are shown. Figure a is the full XPS spectrum of the two materials, proving the element purity in the composite material. Figure bd is the high-resolution spectrum of Ti2p, O 1s and Cu 2p of the two materials, indicating that copper is in the +2 oxidation state and there is a Cu-O-Ti bond, proving that TiO2 and CuO are well combined;
[0067] Comparative Example 2:
[0068] Referring to Example 2, other conditions remain unchanged and the catalyst is original titanium dioxide.
[0069] The scanning electron microscope was used to obtain the scanning electron microscope images of the microplastics after the reaction in Example 2 and Comparative Examples 1 and 2. Figure 7 As shown, from Figure 7 The changes in the surface morphology of PET under different conditions are reflected in the figure. It can be seen that adding CuO / TiO2-1 composite semiconductor photocatalyst to the microplastics treated with alkaline solution has the most obvious effect on the microplastics, proving that it has a significant degradation effect on the microplastics.
[0070] The solutions after the reaction of Examples 1-4 and Comparative Example 2 were filtered, and the residues were collected, dried, and weighed. The weight loss rates of the microplastics in Examples 1-4 and Comparative Example 2 were calculated as shown in Table 1.
[0071] Table 1 Weight loss rate of microplastics
[0072] Weight loss rate of microplastics % Example 1 44.23 Example 2 85.19 Example 3 61.71 Example 4 80.86 Comparative Example 2 61.42
[0073] As can be seen from Table 1, the weight loss rates of the microplastics in the embodiments are all relatively high, indicating that the method for degrading microplastics using a composite semiconductor photocatalyst provided by the present invention has a high degradation rate for microplastics. By comparing the data of Example 2 and Comparative Example 2, it can be seen that the weight loss rate of Comparative Example 2 is much lower than that of Example 2, indicating that the CuO / TiO2-1 composite semiconductor material provided by the present invention, as a catalyst for photocatalytic degradation of microplastics, has a significant improvement in the degradation of microplastics.
[0074] The above-mentioned embodiments are only several embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but they do not limit the embodiments of the present invention. The present invention effectively improves the disadvantage of low response of titanium dioxide to visible light, promotes the separation of electrons and holes, improves the mobility of electrons and holes, provides a conveniently prepared catalyst for photocatalytic degradation of microplastics at room temperature and pressure, and achieves outstanding technical effects by using composite semiconductor photocatalysts to degrade microplastics.
[0075] It should be further pointed out that, for ordinary technicians in this field, various forms of changes and adjustments can be made without departing from the technical solution of the present invention, and these changes should also be included in the protection scope of the present invention, and will not affect the implementation effect and practicality of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the content of the attached claims, and the specific implementation methods in the description can be used to interpret the content of the claims.
Claims
1. A method for degrading microplastics using a composite semiconductor photocatalyst, characterized in that: The composite semiconductor photocatalyst comprises transition metal copper powder and semiconductor material titanium dioxide, and the method comprises the following steps: 1) Preparation of composite semiconductor photocatalysts Setting different mixing ratios, the two substances in the catalyst, transition metal copper powder and semiconductor material titanium dioxide, were processed by calcination; 2) Pretreatment of microplastics Microplastics were pretreated with alkaline solution; 3) Add photocatalyst to photocatalytically degrade microplastics The photocatalyst obtained in step 1) is added to the alkaline solution containing microplastics treated with alkali in step 2), and the microplastics are photocatalytically degraded using a xenon lamp to simulate sunlight; The mass ratio of copper powder to titanium dioxide is 0.5:1 to 2:
1.
2. The method for degrading microplastics using a composite semiconductor photocatalyst according to claim 1, characterized in that: In step 1), the mass ratio of copper powder to titanium dioxide is 1:
1.
3. The method for degrading microplastics using a composite semiconductor photocatalyst according to claim 1, characterized in that: The treatment of the catalyst in step 1) comprises the following steps: S1. Disperse copper powder and titanium dioxide in anhydrous ethanol and continue stirring; S2. The solution obtained in S1 was filtered under reduced pressure to obtain a filter cake; S3. The filter cake obtained from S2 was placed in a drying oven for drying; S4. Pour the powder obtained by drying S3 into a crucible, put it into a muffle furnace for calcination, and obtain a composite semiconductor photocatalyst after cooling.
4. The method for degrading microplastics using a composite semiconductor photocatalyst according to claim 3, characterized in that: In step S1, the amount of anhydrous ethanol is 150 ml, and the stirring time is 2 hours; in step S3, the drying temperature is 50° C., and the time is 6 hours; in step S4, the calcination temperature is 450° C., and the time is 2 hours.
5. The method for degrading microplastics using a composite semiconductor photocatalyst according to claim 1, characterized in that: The specific method in step 2) is: add 2g of microplastics to 10M, 50ml of KOH solution, stir at a constant temperature of 60°C for 2h, and use it directly as a reaction raw material after cooling.
6. The method for degrading microplastics using a composite semiconductor photocatalyst according to claim 1, characterized in that: The specific method in step 3) is as follows: 100 mg of the composite semiconductor catalyst obtained in step 1) is added to the alkaline solution containing microplastics obtained in step 2), and the mixture is placed on a magnetic stirrer under a xenon lamp at 600 mW / cm 2 The light intensity is 2h.
7. The method for degrading microplastics using a composite semiconductor photocatalyst according to claim 1, characterized in that: Microplastics are polyethylene terephthalate particles with a particle size of 100 μm.
8. A method for degrading microplastics using a composite semiconductor photocatalyst according to any one of claims 1 to 7, characterized in that: The weight loss rate of microplastics after photocatalytic degradation of microplastics by composite semiconductor photocatalysts is 44.23-85.19%.
Citation Information
Cited By
Composite material for degrading micro-plastics and preparation method thereof
CN121042058A
A composite material for degrading microplastics and a method of making the same
CN121042058B